1989
DOI: 10.1172/jci114257
|View full text |Cite
|
Sign up to set email alerts
|

Cl- secretion induced by bile salts. A study of the mechanism of action based on a cultured colonic epithelial cell line.

Abstract: When applied to the basolateral (serosal) side of the T84 coIonic epithelial monolayer, taurodeoxycholate caused net Clsecretion in a dose-dependent manner with a threshold effect observed at 0.2 mM. In contrast, when applied to the apical (luminal) surface, concentrations of taurodeoxycholate below 1 mM had little or no effect. Only when the concentration of taurodeoxycholate present on the apical side was 2 1 mM did apical addition results in an electrolyte transport effect. This apical effect on electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 32 publications
3
71
0
Order By: Relevance
“…Although not directly investigated in the present model, this might also apply to the prosecretory effect of TDC. In accord with this, bile salts do not increase cAMP and cGMP colonic intracellular concentrations (Dharmsathaphorn et al, 1989). Nevertheless, in our experiments though the colon was stripped, a paracrine activity cannot be completely excluded.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although not directly investigated in the present model, this might also apply to the prosecretory effect of TDC. In accord with this, bile salts do not increase cAMP and cGMP colonic intracellular concentrations (Dharmsathaphorn et al, 1989). Nevertheless, in our experiments though the colon was stripped, a paracrine activity cannot be completely excluded.…”
Section: Discussionsupporting
confidence: 84%
“…A schematic representation of the mechanisms for Cl -secretion induced by TDC in proximal colon mucosa. TDC activates the Ca 2+ -dependent K + channels-rSK4-on the basolateral membrane by increasing the extracellular Ca 2+ influx (Dharmsathaphorn et al, 1989). The activation of these channels hyperpolarizes the membrane potential, provides the Na + /K + /2Cl -basolateral influx, thereby the driving force for the apical exit of Cl -ions throughout the CFTR.…”
Section: Measurement Of Electrophysiological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the lung, where hSK4 also is expressed, a charybdotoxin-sensitive SK-like channel is thought to hyperpolarize airway epithelia in response to agonists that elevate intracellular Ca 2ϩ and cAMP, thereby facilitating apical Cl Ϫ secretion (35,36). In the colon, activation of Ca 2ϩ -dependent K ϩ channels again appears to be coupled to apical Cl Ϫ secretion (34,54,55). Although we did not examine colonic mRNA for the presence of hSK4, ESTs derived from colon match hSK4, and a rat homolog of hSK4 has been cloned from a colonic cDNA library (V. Rajendran, personal com-FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that showed bile acid-induced increases in K ϩ currents were performed in nonsmooth muscle preparations (Binah et al, 1987;Kotake et al, 1989;Devor et al, 1993). In particular, an increase in a Ca 2ϩ -sensitive conductance in colonic secretory cells by taurodeoxycholic acid led Dharmsathaphorn et al (1989) to postulate an involvement of Ca 2ϩ -dependent K ϩ channels in taurodeoxycholic acid effects on secretion in these cells. These previous studies did not address the particular channel type targeted by bile acids.…”
Section: Possible Role Of Bile Acid Activation Of Bk Ca Channels In Bmentioning
confidence: 99%